Modeling the impact of reaction-diffusion processes within a polyethylene glycol-based hydrogel coating in a microbial electrochemical cell - Korn, Xandria (Kansas State University, 2022)
Microbial electrochemical cells (MECs) provide opportunities for energy production while treating wastewater. The environments these electroactive bacteria are exposed to are dynamic and can be difficult to emulate in a laboratory setting. This report demonstrates the feasibility of a model that simulates reaction-diffusion processes within a protective polyethylene glycol (PEG) - based coating over a bioanode operated as a Microbial Electrolysis Cell ( a MEC) in a wastewater environment. The coating is designed to reduce the transport of undesired chemicals to the biofilm. COMSOL modeling software was used in conjunction with experimentally determined diffusion coefficients, reaction rates, and assumed boundary conditions to create two transient models of chemical concentration throughout the hydrogel. One of these models simulated the introduction of ammonia into the environment. The other model simulated the introduction of hydrogen peroxide into the system when the hydrogel was loaded with hydrogen peroxide degrading (catalase) enzymes. These models can be used to inform experimental conditions that are relevant to the design and development of these coatings. They can be adjusted to simulate the effect of factors such as toxin concentrations within bulk wastewater, the amount of enzyme loaded within the gel, and the reaction kinetics within the gel. With additional testing, this model can be used to optimize the hydrogel system to reduce the impact of toxins on biofilm activity while maintaining flow of nutrients to the microbes for metabolism and energy production.
Keywords: Polyethylene glycol-based hydrogel; Microbial electrochemical cell; Reaction-diffusion simulation